"Doubtful Cases": Intermarried Families in the Post-Holocaust Jewish World. Issue 1 (3rd May 2020) - Yehudai, Ori
ABSTRACT: After World War II, thousands of non-Jews – most of them married to Jewish Holocaust survivors – sought relief and emigration assistance from Jewish aid organisations working in Europe. Yet Jewish organisations and Jewish communities in potential countries of resettlement were often reluctant to assist non-Jews or accept intermarried families into their midst. This article explores these tensions. It argues that appeals from non-Jews compelled Jewish institutions to consider broader questions about the boundaries of the Jewish collective and the tension between the 'Jewish' and 'humanitarian' aspects of Jewish relief work. Ironically, non-Jews played an important role in processes shaping the post-war Jewish world.